2002
DOI: 10.1002/path.1145
|View full text |Cite
|
Sign up to set email alerts
|

Significance of loss of heterozygosity of the RB1 gene during tumour progression in well‐differentiated liposarcomas

Abstract: Tumour progression can be investigated in liposarcomas showing a transition from a low-grade well-differentiated (WD) to a high-grade dedifferentiated (DD) variant. As RB1 gene alterations are common defects in sarcomas, this study examined the frequency of RB1 loss of heterozygosity (LOH) in a group of 14 well-differentiated liposarcomas (WDLs) and 17 well-differentiated/dedifferentiated liposarcomas (WD/DDLs), using a microdissection approach (PALM laser pressure catapulting) that allows the two histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…5,6 Schneider-Stock et al investigated RB1-LOH in two microdissected components of 11 dedifferentiated liposarcoma patients, and RB1-LOH was detected in all the dedifferentiated components, using four intragenic RB1 markers and restriction fragments analysis. 7 In our present study, LOH for one or more markers out of five microsatellite markers at 13q12-14 was found in 15 out of 25 (60%) cases with dedifferentiated component and in three out of 24 (12.5%) cases with well-differentiated component. We detected LOH at D13S153, one of the five microsatellite markers located within intron 2 of the RB1 gene, in 13 out of 24 (54%) dedifferentiated components and in two out of 23 (8.7%) well-differentiated components.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…5,6 Schneider-Stock et al investigated RB1-LOH in two microdissected components of 11 dedifferentiated liposarcoma patients, and RB1-LOH was detected in all the dedifferentiated components, using four intragenic RB1 markers and restriction fragments analysis. 7 In our present study, LOH for one or more markers out of five microsatellite markers at 13q12-14 was found in 15 out of 25 (60%) cases with dedifferentiated component and in three out of 24 (12.5%) cases with well-differentiated component. We detected LOH at D13S153, one of the five microsatellite markers located within intron 2 of the RB1 gene, in 13 out of 24 (54%) dedifferentiated components and in two out of 23 (8.7%) well-differentiated components.…”
Section: Discussionsupporting
confidence: 55%
“…32 Using immunohistochemical methods, the present study demonstrated the expression of pRb to be abnormal in 18 dedifferentiated components and in nine welldifferentiated components, results which are similar to those observed in a previous study. 7 These results suggest that pRB plays a role in dedifferentiation from well-differentiated liposarcoma to dedifferentiated liposarcoma, through the alteration of the coding gene RB1, or through the interaction of CDK4 or MDM2, which are considered to be expressed at a higher level in dedifferentiated component than in well-differentiated component, as described above. pRB has been shown to promote adipocyte differentiation by enhancing the DNA-binding and transactivation activity of C/EBPb, and/or by inhibiting Ras signaling to suppress the activation of the ERK1/2 MAPKs.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Each row represents a single chromosomal subregion, each column shows the chromosomal status for a single tumour sample. Selected, cluster-associated chromosomal subregions are indicated on the right gested an association between dedifferentiation and the altered expression of specific proteins such as MDM2, p53, H-ras, β-catenin, and retinoblastoma protein [12,[26][27][28][29]. Also, chromosomal imbalances additionally to overrepresent 12q13-q15 were more frequent in DDLS than in WDLS [19].…”
Section: Discussionmentioning
confidence: 99%